2013
DOI: 10.1002/mats.201300156
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Functional Group Distribution in Copolymerization: A Comparison of Deterministic and Stochastic Approaches

Abstract: The distribution of functional groups in polymer chains produced in radical copolymerization by starved‐feed semibatch operation is simulated using three different methodologies. Even under perfect control of the overall copolymer composition, a significant fraction of the polymer chains produced contain no functionality. A deterministic model is formulated to separately track the homopolymer chains that are produced without the desired functionality, a Monte Carlo (MC) model is written to represent the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(102 citation statements)
references
References 20 publications
(27 reference statements)
1
99
0
Order By: Relevance
“…Similarly, for statistical FRP copolymerization involving one functional comonomer in a low overall amount (5 mol%), Ali Parsa et al [36] recently found by means of deterministic and stochastic simulations that half of the polymer chains do not contain this functional comonomer under starved-feed conditions. Importantly, such mismatch between the expected and actual copolymer composition would not be captured by a kinetic model description without an explicit differentiation between polymer chains possessing a given number of functional comonomer units.…”
Section: Batch Proceduresmentioning
confidence: 96%
“…Similarly, for statistical FRP copolymerization involving one functional comonomer in a low overall amount (5 mol%), Ali Parsa et al [36] recently found by means of deterministic and stochastic simulations that half of the polymer chains do not contain this functional comonomer under starved-feed conditions. Importantly, such mismatch between the expected and actual copolymer composition would not be captured by a kinetic model description without an explicit differentiation between polymer chains possessing a given number of functional comonomer units.…”
Section: Batch Proceduresmentioning
confidence: 96%
“…The values of required reaction rate constants were extracted from the literature and are summarized in Table 3 . [ 10 ] …”
Section: Copolymerization Temperature 138°cmentioning
confidence: 97%
“…(1) Initiator dissociation Reaction scheme applied to copolymerization. [ 10 ] Initiator molecular weight 132 g mol −1…”
Section: Model Development and Simulationmentioning
confidence: 99%
See 2 more Smart Citations